Yield and Composition of the Essential Oil of Basil on Plant Growth Regulators Application - Ono, E. O. [UNESP]; Rodrigues, J. D. [UNESP]; Barreiro, A. P. [UNESP]; Marques, M. O. M. (Allured Publ Corp, 2011)
This study aimed at evaluating the effect of plant growth regulators on the yield and composition of the essential oil of basil (Ocimum basilicum L.). The experiment was conducted in a greenhouse and the treatments consisted of application of GA(3), ethephon and kinetin at 100 mg/L. Applications were performed at 30, 50 and 70 clays after sowing, respectively, and essential oil yield was assessed at 90 clays after sowing in two harvesting times: 10 Am and 5 P;A. Thus, samples of 100 g shoot (stem plus leaves) and 50 g inflorescences were separated in order to isolate the oil and estimate its volume. To analyze the oil composition, oil samples were analyzed by GC/MS. Plants treated with ethephon had the highest essential oil yield, which were the lowest in those treated with GA(3). The harvest performed at 10 Am had the highest oil yield. The components identified in the oil were linalool, geraniol, eugenol, alpha-guaiene, germacrene D, (E,E)-alpha-farnesene and epi-alpha-cadinol. Treatment with kinetin increased linalool and eugenol levels, whereas ethephon treatment increased eugenol content.
Keywords: Ocimum basilicum; Lamiaceae; essential oil; linalool; eugenol